2013
DOI: 10.5812/ijem.5034
|View full text |Cite
|
Sign up to set email alerts
|

GnRH Analogues in the Prevention of Ovarian Hyperstimulation Syndrome

Abstract: The GnRH analogue (agonist and antagonist GnRH) changed ovarian stimulation. On the one hand, it improved chances of pregnancy to obtain more oocytes and better embryos. This leads to an ovarian hyper-response, which can be complicated by the ovarian hyperstimulation syndrome (OHSS). On the other hand, the GnRH analogue can prevent the incidence of OHSS: GnRH antagonist protocols, GnRH agonist for triggering final oocyte maturation, either together or separately, coasting, and the GnRH analogue may prove usefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 98 publications
(111 reference statements)
0
10
0
1
Order By: Relevance
“…Different studies on human and animal models have shown that in OHSS, some mediatory compounds are released from the ovaries that increase capillary permeability and liquid assembly in the peritoneal cavity [2,22,23]. Although the pathophysiology of this syndrome is not completely revealed, it seems that the release of vasoactive and angiogenic substances lead to leakage, hyperpermeability of liquid and shift of fluids from blood vessels into the extravascular space and have a role in this syndrome [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different studies on human and animal models have shown that in OHSS, some mediatory compounds are released from the ovaries that increase capillary permeability and liquid assembly in the peritoneal cavity [2,22,23]. Although the pathophysiology of this syndrome is not completely revealed, it seems that the release of vasoactive and angiogenic substances lead to leakage, hyperpermeability of liquid and shift of fluids from blood vessels into the extravascular space and have a role in this syndrome [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important signs of this syndrome is the enlargement of ovaries in which luteal and hemorrhagic cysts along with a shift of liquids into the peritoneal cavity. Polishuk et al reported that the release of various compounds from the ovaries leads to an increase in capillary permeability and, hence, liquid shift from the intravascular compartment into the peritoneal cavity [2,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GnRH agonistinin reseptör düze-yinde antagonistin yerine geçmesiyle reseptör aktive olacak ve gonadotropin salınımı olacaktır (flare etki). 49 …”
Section: Gnrh Agoni̇st Vs Antagoni̇st Protokollerunclassified
“…Research published on the issue reveals that the frequency of ovarian hyperstimulation syndrome varies from 0.5% to 33% with different schemes of ovulation stimulation and does not reveal a downward trend. Severe forms of the syndrome that require hospitalization have been diagnosed in 0.2-10% of all cases [15].…”
Section: Introductionmentioning
confidence: 99%